A pivotal role for the activation of TRPV3 channel in itch sensations induced by the natural skin sensitizer carvacrol - CUI Ting-ting; WANG Gong-xin; WEI Ning-ning; WANG KeWei (Acta Pharmacologica Sinica, 2018)
Abstract Itching is an intricate, common symptom of dermatologic and systemic diseases, and both TRPV3 and TRPA1 channels have been suggested to function as downstream effector targets. But the relative contributions of TRPV3 and TRPA1 to itch sensation in vivo remain unclear. To dissect the role of TRPA1 or TRPV3 in the cutaneous sensation of itching, we took the advantage of a natural compound carvacrol from oregano, and examined its effect on the induction of scratching behavior in mice. We showed that the intradermal injection of carvacrol (0.01%, 0.1% and 1%, 50 μL) induced scratching in a concentration-dependent manner. But in TRPV3-knockout mice, the scratching induced by carvacrol (1%, 50 μL) was markedly decreased by approximately 64% (from 275 scratching bouts down to 90) within 60 min. Further analysis revealed that TRPV3-knockout caused a reduction of scratching bouts for approximately 40% in the first 20 min (the initial phase), whereas the scratching bouts were reduced by approximately 90% in the last 40 min (the sustained phase). These results were in consistence with those in our whole-cell recordings in HEK-293T cells expressing either TRPA1 or TRPV3: carvacrol exhibited similar potencies in activating either TRPA1 or TRPV3, but carvacrol-activated TRPA1 current showed a rapid desensitization, which was reduced by approximately 90% within 5 min before a complete washout, whereas carvacrol-induced TRPV3 current showed a slow desensitization that caused less than 30% of current reduction in 10 min and left a significant residual TRPV3 current after washout. Our results demonstrate that carvacrol from plant oregano is a skin sensitizer or allergen; TRPV3 is involved in the initial phase and the sustained phase of pruritus, whereas TRPA1 likely contributes to the initial phase.